2008
DOI: 10.1309/1yu0d34vjknucgt1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hemoglobin C and S Traits on the Results of 14 Commercial Glycated Hemoglobin Assays

Abstract: Glycated hemoglobin is widely used in the management of diabetes mellitus. At least 300,000 Americans with diabetes mellitus have the hemoglobin (Hb) C or S trait. The accuracy of HbA1c methods can be adversely affected by the presence of these traits. We evaluated the effects of HbC and HbS traits on the results of 14 commercial HbA1c methods that use boronate affinity, enzymatic, immunoassay, and ion exchange methods. Whole blood samples from people homozygous for HbA or heterozygous for HbC or HbS were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 12 publications
(11 reference statements)
4
34
2
Order By: Relevance
“…This finding confirms that whenever we use an immunoassay to measure HbA1c, there is a probability that patients with the HbS trait will be undertreated due to the lower HbA1c results produced, as the immunoassay would be unable to identify the presence of hemoglobin variants. However, in a study by Mongia SK et al, common Hb traits, such as HbAS and HbAC, did not interfere with the Bio-Rad Variant II Turbo CE-HPLC HbA1c NA not available assay used in this study [27]. In contrast with the above studies, we found no significant differences in the HbA1c results for our SCT patients from either HPLC or immunoassays.…”
Section: Discussioncontrasting
confidence: 86%
“…This finding confirms that whenever we use an immunoassay to measure HbA1c, there is a probability that patients with the HbS trait will be undertreated due to the lower HbA1c results produced, as the immunoassay would be unable to identify the presence of hemoglobin variants. However, in a study by Mongia SK et al, common Hb traits, such as HbAS and HbAC, did not interfere with the Bio-Rad Variant II Turbo CE-HPLC HbA1c NA not available assay used in this study [27]. In contrast with the above studies, we found no significant differences in the HbA1c results for our SCT patients from either HPLC or immunoassays.…”
Section: Discussioncontrasting
confidence: 86%
“…In a series of publications between 2000 and 2008, it was noted that HbS does not interfere with HPLC method 1 and immunoturbidimetric methods, [22][23][24] an observation that this study has confirmed.…”
Section: Discussionsupporting
confidence: 66%
“…An international consensus committee has recommended that results should be reported worldwide in both SI units (mmol ⁄ mol) and derived NGSP ⁄ DCCT units (%) [38]. Acknowledging the limitations of the ADAG study, the consensus committee decided against the routine HbC [92] HbE [93] HbD [93] Hereditary persistence of HbF [94] Chemical derivatives of haemoglobin Carbamylated haemoglobin (e.g. as a result of uraemia) [95] Acetylated haemoglobin (e.g.…”
Section: Reporting Hba 1c Resultsmentioning
confidence: 99%